Developing CAS models in immunology teaching - Adnan, Nurhidayah; Yaacob, Yuzita; Hassan, Mohammad Khatim; Mohd. Salleh, Hamzah; Noorbatcha, Ibrahim Ali (2009)
How can mathematical modelling be integrated withcomplex network of biological system in comprehensive education? There are mutual agreements between academia from various fields that mathematical modelling is an important part of the curriculum. Immunology is a complex subject and for student to fully understand its complex interaction at molecular level requires computer supported models. This research tries to resolve the ever emerging problem of teaching immunology in higher education. The main objective is to develop multimedia educational software to enhance immunology teaching, with the use of a Computer Algebra System (CAS) that fully utilizes mathematical equation, modelling and simulation of complex network of gene regulation and metabolism. A survey was conducted among students in higher learning institutions, and the result clearly shows that the current teaching method is not feasible to the current learning style. To overcome this, new teaching techniques to support the required understanding need to be introduced. With the development of this educational package that uses new modelling and simulation techniques hopefully can aid in teaching some of immunology courses.